Households' willingness to donate for the conservatatioin and management of the Ayer Keroh recreational forest, Melaka - Matthew, Nitanan Koshy; Mohd Sharif, Farah Hanim; Shuib, Ahmad (Penerbit UMT, 2021)
The benefits of recreational forests are not only for tourists, but also for households and residents living in the surroundings of the forests. Such benefits include supporting services, provisioning services, regulating services, and cultural services. Very limited studies have determined the value allotted by residents to a recreational forest, which in turn would result in incomplete decision-making processes concerning forest conservation. The aim of this study is to determine households’ willingness to donate for the conservation and management of the Ayer Keroh Recreational Forest (AKRF) in Melaka. This study involved 300 households that were situated adjacent to the park. A total of 300 households were equally selected using stratified and systematic sampling in seven (7) small villages in Ayer Keroh. The findings from a Probit regression analysis revealed that the idea of enhancing conservation efforts, age, and income had a significant relationship with the willingness to donate. An estimation of the willingness to donate using the Double-Bound CVM amounted to RM17.74 per household per annum. The finding is important in order to understand the value allotted by the residents to the forest while, nevertheless, providing policy-relevant information for forest management and conservation purposes of a recreational forest.